Postpartum Depression and Risk Factors among Vietnamese Women - Do, Thi Kim Ly (Biomed Res Int, 2018)
Postpartum depression (PPD) places a burden on maternal health. PPD exerts a negative impact on mothers' health and children's life. The purpose of this research was to identify the prevalence of PPD and the risk factors contributing to PPD. Therefore, a cross-sectional quantitative study was conducted. 116 women were categorized into two groups. One category included new mothers who received scores of Edinburgh Postpartum Depression Scale (EPDS) 12 or more. The other category included mothers who received scores less than 12. Descriptive statistic and then binary logistic regression were also performed. For EPDS ≥ 12, the prevalence of PPD was 27.6% among new mothers during the first year after delivery. Level of education, diseases during pregnancy, being the first-time mothers, dissatisfaction about family, and limited communication and interaction with others were significant predictors of PPD.